Assistance for Small and Medium Industries in Increasing Entrepreneurship by Applying Safety Aspects of the Work Environment in Cikarang City - Edwina Rudyarti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Community service activities are carried out in the Small and Medium Industry (IKM), which is a home industry that has at least 4 workers and a maximum of 19 people. This community service activity is carried out with the aim of providing employees with an understanding of the importance of OSH at work and education on the proper and correct application of PPE (Personal Protective Equipment) at work, as well as providing training related to entrepreneurship development for additional income apart from income from making furniture, aspects taken in this community service activity is related to occupational safety management and also product marketing strategies in which business activities can continue to develop in the future by paying attention to and implementing supporting factors in carrying out business activities. Socialization, education and training activities are tailored to the problems and needs faced by partners. The method of implementing the activity consists of 5 stages, namely the initial stage of observation and identification of problems in the workplace environment, the second stage of socialization and education regarding the importance of OSH, the third stage of mentoring in the application of PPE in the field, the fourth stage of entrepreneurship program training for marketing managerial strategies. The results of community service activities, mentoring small furniture industry businesses are 1.